The genealogical imagination : two studies of life over time - Jackson, Michael, 1940- (Duke University Press, 2021)
"Michael Jackson juxtaposes ethnographic and imaginative writing to explore intergenerational trauma and temporality, showing how genealogy becomes a powerful model for understanding our experience of being in the world."--